2013
DOI: 10.1016/j.rmed.2012.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical significance of circulating autoantibodies in idiopathic pulmonary fibrosis

Abstract: Background: The clinical significance of circulating autoantibodies in idiopathic pulmonary fibrosis is unclear. The objective of this study was to determine the frequency and clinical significance of circulating autoantibodies in idiopathic pulmonary fibrosis. Methods: We measured an extensive panel of autoantibodies (including rheumatoid factor, anti-cyclic citrullinated peptide, and anti-nuclear antibodies by immunofluorescence) associated with connective tissue disease or vasculitis in a cohort of well-cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
3
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 18 publications
5
81
3
8
Order By: Relevance
“…Among patients with IPF, no differences were found in clinical, functional or imaging characteristics between those with and without auto-antibodies. When adjusted for age, sex, smoking and forced vital capacity, circulating antibodies (antinuclear antibodies with titre o1:320 or rheumatoid factor o60 UI?mL -1 ) seem to be associated with longer transplant-free survival time [48]. Overall, these observations suggest that the frequency of circulating autoantibodies in patients with IPF is similar to that of healthy controls, with unclear impact on survival.…”
Section: Ctd Features May Be Missed In the Diagnostic Approach Of Ildmentioning
confidence: 83%
See 1 more Smart Citation
“…Among patients with IPF, no differences were found in clinical, functional or imaging characteristics between those with and without auto-antibodies. When adjusted for age, sex, smoking and forced vital capacity, circulating antibodies (antinuclear antibodies with titre o1:320 or rheumatoid factor o60 UI?mL -1 ) seem to be associated with longer transplant-free survival time [48]. Overall, these observations suggest that the frequency of circulating autoantibodies in patients with IPF is similar to that of healthy controls, with unclear impact on survival.…”
Section: Ctd Features May Be Missed In the Diagnostic Approach Of Ildmentioning
confidence: 83%
“…As compared to IPF patients with negative autoimmune biology, those with auto-antibodies are more likely to exhibit ground-glass attenuation, have more significant honeycombing and a higher extent of ILD at HRCT but similar survival [7]. Similarly, LEE et al [48] tested 67 patients with IPF and 52 healthy controls for the presence of an extensive panel of auto-antibodies and found no difference in the frequency or type of antibodies between IPF and control subjects (22% versus 21%), probably reflecting auto-antibodies of unknown significance in an ageing population rather than genuine UCTD (although long-term follow-up was not available). Among patients with IPF, no differences were found in clinical, functional or imaging characteristics between those with and without auto-antibodies.…”
Section: Ctd Features May Be Missed In the Diagnostic Approach Of Ildmentioning
confidence: 96%
“…The role of autoimmunity is better delineated in other ILDs, such as idiopathic NSIP [88], but it is still unclear in IPF. LEE et al [89] compared 67 IPF patients to 52 healthy controls and found positive autoantibodies in 22% of IPF patients and 21% of healthy controls, without significant differences in the types of autoantibodies or clinical characteristics between IPF, with and without circulating autoantibodies. The presence of circulating autoantibodies was associated with longer TFS time on adjusted analysis; however, the significance varied depending on which statistical model was used (HR 0.22-0.47, p-value 0.02-0.17).…”
Section: Advances In Understanding the Pathogenetic Mechanisms Of Ipfmentioning
confidence: 99%
“…However, in our case there were no clinical, serological or pathological findings suggestive of an underlying systemic disease. Patients with IPF may have mildly positive anti-nuclear antibody and/or rheumatoid factor serology, although their frequency does not appear to differ from healthy, age-matched controls [11]. Finally, despite his exposure to amiodarone, we confidently excluded that our patient had a drug-induced ILD based on distinctive radiological, BAL and pathological findings.…”
Section: Excluding Known Causes Of Pulmonary Fibrosismentioning
confidence: 76%